2013
DOI: 10.1007/s13277-013-1019-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of VEGF expression in osteosarcoma: a meta-analysis

Abstract: Vascular endothelial growth factor (VEGF) is considered as a prime mediator of angiogenesis and has been implicated in carcinogenesis and metastasis. Various studies examined the relationship between VEGF overexpression with the clinical outcome in patients with osteosarcoma but yielded conflicting results. Electronic databases updated to April 2013 were searched to find relevant studies. A meta-analysis was conducted with eligible studies which quantitatively evaluated the relationship between VEGF overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 32 publications
3
44
0
1
Order By: Relevance
“…[21] Serum VEGF levels are elevated in many primary tumors, including osteosarcoma. [2225] A study also showed the overexpression of VEGF mRNA in a murine model of highly metastatic osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Serum VEGF levels are elevated in many primary tumors, including osteosarcoma. [2225] A study also showed the overexpression of VEGF mRNA in a murine model of highly metastatic osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although somewhat controversial, increased VEGF expression has been associated with poor outcomes in patients with osteosarcoma (4,29). Here we also show that chemotherapyna€ ve human osteosarcoma cells variably coexpress VEGF/ VEGFR1.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is overexpressed by the vast majority of solid tumors (4,5). VEGF includes multiple isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the survival and proliferation of highly aggressive OS cells was dependent on autocrine (17). Numerous studies have suggested that VEGF expression may act as a biomarker of prognosis in OS patients (26)(27)(28). A previous study reported that patients with high VEGF expression had significantly reduced disease-free survival and overall survival rates compared with OS patients with low or negative VEGF expression (28).…”
Section: Discussionmentioning
confidence: 99%